Traditional healing of Lio People in Flores, Indonesia: The source of knowledge - Dwi Prasetyo, Budiyanto; Saragih, Grace Serepina; Fauzi, Ridwan; Hidayat, Muhamad Yusup; Septina, Ane Dwi (Ethnobotany Research and Applications, 2024)
Background: Ethnomedicine research employing the positivist paradigm has documented the types and benefits of flora and fauna used in traditional medicine. However, it has failed to explain the production of ethnomedical knowledge. A multidisciplinary approach provides opportunities for ethnomedicine research to explore the role of traditional knowledge sources in producing ethnomedical knowledge and analyze the impact of modern knowledge dominance on the existence of ethnomedicine. This study aims to document Lio's traditional healing practices and investigate the sources of their knowledge and transmission methods. Methods: Lio’s people ethnomedicinal data and traditional healing practices were gathered from seven Lio’s traditional healers through semi-structured questionnaires. Ethnomedicinal data were quantitatively analyzed using Use Value (UV) and Family Importance Value (FIV). Qualitative data obtained from semi-structured interviews were analyzed using thematic analysis techniques. Results: This study concludes that the Lio people possess significant potential in terms of knowledge and raw materials for traditional medicine. Dreams serve as a medium for Lio herbalists to obtain and pass on ethnomedical knowledge to the next generation. The younger generation's interest in pursuing a career as herbalists has declined due to the modernization of the healthcare system in rural areas. Conclusions: The communities of the Rwenzori region depend a lot on herbal medicine to treat various diseases irrespective of the availability of modern health care. Keywords: Dreams; Ethnomedicine; Traditional knowledge; Traditional healing practices